Comments on the article “Terminological aspects of blood pressure measurement” by G.G. Efremushkin - A. N. Rogoza (Кардиоваскулярная терапия и профилактика)
Comments on the article “Terminological aspects of blood pressure measurement” by G.G. Efremushkin